Analyzing the Influence of Organizational Culture in Projects using Last Planner System (Construction Economics and Building, 2023)
The use of lean tools and techniques to reduce waste from the workflow has been prominently gaining popularity in the construction industry worldwide. Last Planner System (LPS) is one of such distinguished tools used by construction majors. Many research suggests that LPS plays a significant role in improving the collaboration among the project team members and the firm's organizational culture. This paper reports the intermediating effect of organizational culture on construction projects that implement the Last Planner System and also identifies the effect of LPS on the project's operational performance. Various survey items pertaining to each variable was identified and was validated through Content Validation. All the established items were then compiled into a questionnaire, and multiple data were collected from a variety of projects. The data were analyzed using bivariate correlation and multiple regression analysis. Additionally, the "organizational culture assessment instrument" was utilized to compare the organizational cultures of various construction sites. It was discovered that the Last Planner System had a positive but negligible relationship with the operational performance of the project, and the organizational culture. It was observed that all the projects implementing LPS had a balance culture. The contribution of this work is the knowledge that the implementation of the Last Planner System is not necessarily enhanced by culture to a great extent. However, it has a positive impact on both the operational performance of the project and the organizational culture.